Effective elimination of tetracycline antibiotics via photoactivated SR-AOP over vivianite: A new application approach of phosphorus recovery product from WWTP - Xiao-Hong Yi; Tian-Yu Wang; Hong-Yu Chu; Ya Gao; Chong-Chen Wang; Yu-Jia Li; Long Chen; Peng Wang; Huifen Fu; Chen Zhao; Liu, Wen (Chemical Engineering Journal, 2022)
Fe3(PO4)2·8H2O (Vivianite) is one of the potential phosphorus recovery products from wastewater treatment plant (WWTP). In this study, we first discovered that vivianite can effectively photoactivate peroxodisulfate (PDS) to produce some reactive oxygen species (ROS) for tetracycline antibiotics (TCs) degradation. The results demonstrated that vivianite could efficiently activate PDS to achieve 100% removal of TCs under LED UV light (UVL), visible light (VL) or real solar light (SL) irradiation within 10 min, respectively. More importantly, ca. 80%, 78% and 40%∼58% of TOC removal efficiencies were achieved under UVL, VL and SL irradiation within 30 min, respectively. As well, toxicological simulation and antibacterial studies showed that the aquatic toxicity of the TCs intermediates was lower than those of the original TCs. This work provided new insights into the application of photoactivated sulfate radical-advanced oxidation process (SR-AOP) for organic pollutants degradation over vivianite, which may encourage the recovery and utilization of vivianite in the wastewater treatment process.
Keywords: Degradation; Peroxydisulfate; Photoactivation; Tetracycline antibiotics; Vivianite